(untitled) - Rayport, Jeffrey F. (Boston, MA., 2003)
The text focus is on what a manager needs to know about Internet infrastructure, strategy formulation and implementation, technology concepts, public policy issues, and capital infrastructure in order to make effective business decisions. This is presented in a framework for the study and practice of e-Commerce with business strategy at the core surrounded by four infrastructures; the technology infrastructure that underlies the Internet, the media infrastructure that provides the content for businesses, public policy regulations that provide both opportunities and constraints, and the capital infrastructure that provides the money and capital to run the businesses. Within this framework, the authors provide a deep exploration of core concepts of online strategy and associated enablers enriched by a wide variety of examples, case studies, and explanations culled directly from practice.
Keywords: Electronic commerce